Applying Restorative Justice to Resolve Minor Assault Cases - Hendro Widodo; Raul Gindo Cahayao; Reza Octavia Kusumaningtyas (Jurnal Justice Dialectical, 2024)
To facilitate non-litigation case resolution, the criminal justice system in Indonesia has implemented restorative justice through the Prosecutor's Regulation and the Police Regulation. Nevertheless, the practical implementation of restorative justice in cases of minor assault continues to encounter a variety of challenges. Consequently, this investigation aims to evaluate how restorative justice is implemented to resolve instances of minor assault. This investigation implements a normative legal research methodology. The study's findings suggest that Indonesia's criminal justice system has initiated the implementation of restorative justice as an alternative to traditional court procedures for resolving cases, particularly minor crimes. This approach emphasizes dialogue and the restoration of relationships. This method aims to mitigate the burden on judicial institutions, prevent societal resentment, and reduce criminalization and stigma. Nevertheless, its implementation is impeded by a lack of understanding, limited legal regulations, and minimal support from the community and victims. To achieve success, it is necessary to implement more stringent regulations, provide law enforcement officers with training, and engage the community.